Enhanced electrocatalytic performance of TiO2 nanoparticles by Pd doping toward ammonia synthesis under ambient conditions. Issue 19 (17th February 2022) - Chen, Hai-jun; Deng, Guo-rong; Feng, Zhe-sheng; Xu, Zhao-quan; Yang, Meng-yao; Huang, Yan; Peng, Qiling; Li, Tingshuai; Wang, Yan
Abstract : Pd-doped TiO2 nanoparticles as an effective NRR electrocatalyst present a large NH3 yield of 17.4 μg h −1 mgcat. −1 and a high faradaic efficiency of 12.7% at −0.50 V vs. RHE in 0.1 M Na2 SO4 electrolyte. Abstract : The traditional Haber–Bosch process in industry to produce NH3 leads to excessive CO2 emissions and a large amount of energy consumption. Ambient electrochemical N2 reduction is emerging as a green and sustainable alternative method to convert N2 to NH3, but is in sore need of efficient and stable electrocatalysts. Herein, we propose using Pd-doped TiO2 nanoparticles as a high-efficiency electrocatalyst to synthesize NH3 under ambient conditions. The Pd–TiO2 catalyst delivers a large NH3 yield (17.4 μg h −1 mgcat. −1 ) and a high faradaic efficiency (12.7%) at −0.50 V versus reversible hydrogen electrode in a neutral electrolyte, outperforming most Pd- and Ti-based electrocatalysts recently reported for N2 reduction. Most importantly, it also demonstrates extraordinary long-term electrochemical stability.